Can appropriate systemic treatment help protect the cornea in patients with rheumatoid arthritis? A multidisciplinary approach to autoimmune ocular involvement (2018)
Purpose: To correlate rheumatologic with ophthalmic and laboratory findings in patients with rheumatoid arthritis (RA) to identify what effect these have on development of ocular disease. Methods: This is a cross-sectional study of 172 eyes of 86 patients with RA. Patients were examined by a group of rheumatologists. Sociodemographic, clinical, and laboratory data were collected. All patients underwent complete ophthalmologic examination including corneal topography and endothelial cell count. Results: There was no significant correlation between RA-negative prognostic indicators (NPIs) and pathologic corneal findings. Patients using disease-modifying antirheumatic drugs (DMARDs) and antimalarial drugs had greater corneal volumes (mean difference 8.51 mm3, 90% confidence interval [CI], 3.98-13.04, P = 0.004; and 2.24, 90% CI, 0.32-4.54, P = 0.048, respectively). Patients using azathioprine had lower endothelial cell counts compared with those using other drugs (mean difference 180 cells/mm2, 90% CI, 69-291, P = 0.008). Patients using biologic DMARDs had better tear osmolarity values (between 280 and 300 mOsm/L) than patients not using them (mean difference 14.3 mOsm/L, P = 0.022). There was no correlation between NPIs of RA and positive keratoconus screening indices (Spearman correlation OD -0.013, P = 0.91; OS -0.033, P = 0.76). Conclusions: There was no clear correlation between RA-NPIs and pathologic corneal findings in our study. DMARDs treatment may help maintain corneal integrity in our patients and prevented collagenolytic manifestations of RA. Other medications such as azathioprine should be used carefully, as endothelial damage may potentially occur. Copyright © 2018 Wolters Kluwer Health, Inc. All rights reserved.